Factors associated with potentially inappropriate prescriptions and barriers to medicines optimisation among older adults in primary care settings: a systematic review. Issue 4 (18th November 2021) - Xu, Zhijie; Liang, Xujian; Zhu, Yue; Lu, Yiting; Ye, Yuanqu; Fang, Lizheng; Qian, Yi
Abstract : Objective: To identify factors that likely contribute to potentially inappropriate prescriptions (PIPs) among older adults in primary care settings, as well as barriers to medicines optimisation and recommended potential solutions. Design: Systematic review. Eligibility criteria: Quantitative studies that analysed the factors associated with PIPs among older adults (≥65 years) in primary care settings, and qualitative studies that explored perceived barriers and potential solutions to medicines optimisation for this population. Information sources: PubMed, EMBASE, Scopus, CINAHL, PsycINFO, Web of Science, CNKI and Wanfang. Results: Of the 13 167 studies identified, 50 were included (14 qualitative, 34 cross-sectional and 2 cohort). Nearly all quantitative studies examined patient-related non-clinical factors (eg, age) and clinical factors (eg, number of medications) and nine studies examined prescriber-related factors (eg, physician age). A greater number of medications were identified as positively associated with PIPs in 25 quantitative studies, and a higher number of comorbidities, physical comorbidities and psychiatric comorbidities were identified as patient-related clinical risk factors for PIPs. However, other factors showed inconsistent associations with the PIPs. Barriers to medicines optimisation emerged within four analytical themes: prescriber related (eg, inadequate knowledge, concerns of adverse consequences, clinical inertia, lack of communication), patient related (eg, limited understanding, patient non-adherence, drug dependency), environment related (eg, lack of integrated care, insufficient investment, time constraints) and technology related (eg, complexity of implementation and inapplicable guidance). Recommended potential solutions were based on each theme of the barriers identified accordingly (eg, prescriber-related factors: incorporating training courses into continuing medical education). Conclusions: Older adults with more drugs prescribed and comorbidities may have a greater risk of receiving PIPs in the primary care setting, but it remains unclear whether other factors are related. Barriers to medicines optimisation among primary care older adults comprise multiple factors, and evidence-based and targeted interventions are needed to address these difficulties. PROSPERO registration number: CRD42020216258.